Possibilities for qualitative evaluation of the protection area of protective clothing - Dominik Münks; Jasmin Pilgrim; Kyosev Yordan (Communications in Development and Assembling of Textile Products)
Protective clothing, worn for example by police, ambulance and private security services, has the task of protecting against weapon attacks and is becoming increasingly important. International standards specify test methods to ensure the protective effects and classes, but the protective surfaces or the wearing comfort are not defined more detailed in the standards. In the study, a new measurement method is developed and presented for determining the percentage of protected body parts by a stab protective vest. After considering various approaches, the combination of scanned 3D/4D body data and appropriate processing turned out to be the most suitable. With the developed method, the projection of protective surfaces onto scanned bodies or avatars is possible. This study helps defining a key indicator of the protected areas and therefore makes different vest variants more comparable.